Assessing the potentials for deliberative practices in Philippine politics: The various mechanisms of the barangay - Go, Nathan Mishael O. (Animo Repository, 2022)
Innovations in improving the quality of democracy have been of particular interest. More specifically, studies have pointed to the value of democracy, that deliberative democracy has positive effects on politics and society (Michels & Binnema, 2019); democratic deliberation can increase civic virtues such as knowledge on societal issues, trust in representative actors and politicians and the inclination to collective and political action (Grönlund et al., 2010); deliberative democracy is the solution to group polarization and is applicable in deeply divided societies (Curato, Dryzek, Ercan, Hendriks, & Niemeyer, 2017). What started as a normative theory of democracy has been put into practice (Chambers, 2003). Thus, this study, by analyzing the barangay and its various mechanisms aims to take account of the deliberative potentials in the barangay.